Estudio biotico (avifauna) en las gradientes altitudinales de la cordillera occidental de los Andes, en los bosques siempre verde medio y bajo, en el Cantón La Maná, Provincia De Cotopaxi, Ecuador. - Yucailla Carvajal, Alex Geovanny (2024)
The objective of this research was to carry out a biotic study (avifauna) in the altitudinal gradients of the western Andean Cordillera, in the medium and low evergreen forests, in the Canton La Maná, Cotopaxi Province, Ecuador. For this purpose, the current situation of the study area was determined through primary and secondary literature review, in which several monitoring techniques were used. Based on the data collected, a qualitative and quantitative analysis of the individuals recorded in three different sampling points was carried out. In addition, the biodiversity index of each point was determined, which facilitated the elaboration of a catalog listing the species identified in the study area. As a result, 25 species were obtained, which are divided by sampling points such as P1 (Malki Machay) where 18 species, 7 orders and 12 families were found with a conservation status of 90% in minor concern and 10% in vulnerable status, At sampling point P2 (El Turbante), 5 species, 3 orders and 4 families were found with a conservation status of 100% in minor concern and finally, at sampling point P3 (Los Laureles), 7 species, 5 orders and 5 families were recorded with a conservation status of 100% in minor concern. All species identified in the study areas are included in the avifaunal catalog, which provides detailed information on their taxonomic classification, descriptions and conservation status. According to the quantitative results, sampling point 1 showed a medium diversity, while sampling points 2 and 3 showed a low diversity.